Sustainability Lessons from Kanazawa City, Japan - Mammadova, Aida (European Journal of Sustainable Development, 2017)
We have conducted the intensive training fieldwork courses to the environmental and social sectors of the Kanazawa City, and observed how those sectors function in the integrated manners for the sustainable development. Participants were 9 students, from the United Nations University Institute for the Advanced Study of Sustainability and Kanazawa University. Field destinations were divided to the next sectors: renewable energy sectors, urban waste power plants, landfills, recycling facilities, water purification sectors, wastewater management and energy plants, local forestry, city port and fishery, sustainable organic agriculture, traditional crafts and educational sectors of the City. At the end of the course students gave their feedback and recommendations for each sectors. Fieldworks showed the strong interconnection between each sectors, and their sustainable cooperation was clearly observed. Public education was strongly emphasized in each sector. However, several questions were raised after the fieldworks; 1. If such kind of sustainable city model can be implemented for developing countries 2. What will be the main obstacles to achieve sustainability there 3. How can conservation and responsible utilization of natural resources, balanced in sustainable manner. In the future we plan to create the educational fieldwork models for each sustainable sectors, which are practiced in Kanazawa City and implement them as an experimental model in the developing countries. Keywords: Sustainability, Educational Fieldworks, Environment, Conservation